Space deficit in low cost households of Peninsular Malaysia - Yahaya, Nurizan; Ahmad, Halimah (Penerbit Universiti Sains Malaysia, 1993)
Space deficit is one of the problems faced by the low cost housing dwellers because of its minimum floor size and cost. This study examines the space deficit experienced by households residing ill three types of low cost public housing, namely, single story terrace houses, walk-up flats and high rise flats. A total of 914 low cost housing dwellers, ill Peninsular Malaysia were randomly selected and interviewed in this study. The results of the study show that the majority of the households experienced space deficit, with the deficit more severe when the family was larger. The highest deficit was very evident ill the case of bedrooms. Occupancy per bedroom was moderately high, i. e. between two to three persons per bedroom. The occupancy ratio was the highest among the residents of high rise flats, followed by walk-up flats and terrace houses. The occupants in the terrace houses had the opportunity to build additional rooms when the economic conditions permit and were thereby able to reduce the room deficit. A question arises as to whether terrace houses are a better alternative to other types of houses because this type of structure can be adjusted to meet family needs.